Biogeographical regionalization of Kosovo: integrating vegetation, climate and topography - Berisha, Naim; Krasniqi, Elez; Bytyqi, Valbon (Mediterranean Botany, 2025)
Kosovo, located at the intersection of continental, alpine and sub-Mediterranean climatic influences, represents a biogeographical transition zone with high ecological complexity. In this study, three different biogeographical regions are delineated - the continental, the alpine and the sub-Mediterranean region - using an integrative approach combining vegetation, climate and topography. By using updated vegetation mapping, standardized environmental data and K-means clustering, the study shows the spatial organization of vegetation alliances along altitudinal and climatic gradients. The continental region, which covers the widest area, is characterized by temperate deciduous forests and riparian ecosystems, while the alpine region has resilient high mountain vegetation adapted to extreme conditions. The sub-Mediterranean region, which is influenced by Adriatic-Ionian and Aegean climatic elements, is home to thermophilic forests and Mediterranean flora. The transition zones observed between the regions highlight the dynamic interplay of environmental factors that shape Kosovo's biodiversity. This research provides a fundamental framework for conservation planning and biogeographic studies in the Balkans and emphasizes the importance of integrating abiotic and biotic variables in regional classification.